PENGARUH METODE CERDAS, CERMAT, CEPAT DAN TEPAT (C3T) TERHADAP MOTIVASI BELAJAR PKn SISWA KELAS IX SMP NEGERI 40 PEKANBARU - Sari, Putri Siska; Erlinda, Sri; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was motivated by the low motivation to learn PKn student at SMP Negeri 40 Pekanbaru. Formulation of the problem in this research is: "Is there any Influence Learning methods C3T Against Motivation PPKn Class IX SMP Negeri 40 Pekanbaru?".This study aims to determine Is There Influence of Cooperative Learning methods C3T in Improving Learning Motivation PKn Class IX SMP Negeri 40 Pekanbaru ". This research was conducted in SMP Negeri 40 Pekanbaru in June 2017. This research is quantitative descriptive the population in this research is class IX SMP Negeri 40 Pekanbaru.The sample in this study was based technique of "Random Sampling". Where classes are taken into the sample are students of class IXa (experimental grade) were given learning methods C3T, and class IXd (control class) is a student who was given the conventional method and then the data analysis using the homogeneity test and test " t ". Based on the results of the study indicate that there are significant learning motivation among students who use learning methods C3T and conventional methods in SMP Negeri 40 Pekanbaru (t = 8.9> table = 2.00). Where there is an average increase learning motivation PKn experimental class of 22.87 into 30.13 and an average increase learning motivation PPKn control classes of 25.51 into 26.15. Thus the hypothesis which says there are significant learning methods use C3T on motivation to learn PKn class IX SMP Negeri 40 Pekanbaru, unacceptable.Keywords:C3T, Motivation to learn.